Copper(II) Complexes with Schiff Bases Containing a Disiloxane Unit: Synthesis, Structure, Bonding Features and Catalytic Activity for Aerobic Oxidation of Benzyl Alcohol. Issue 9 (4th February 2013) - Soroceanu, Alina; Cazacu, Maria; Shova, Sergiu; Turta, Constantin; Kožíšek, Jozef; Gall, Marian; Breza, Martin; Rapta, Peter; Mac Leod, Tatiana C. O.; Pombeiro, Armando J. L.; Telser, Joshua; Dobrov, Anatolie A.; et al.
Abstract: Mononuclear copper(II) salen‐type Schiff base complexes, Cu II L 1–5 [H2 L 1 to H2 L 5 = tetradentate N, N, O, O ligands derived from 2‐hydroxybenzaldehyde, 2, 4‐dihydroxybenzaldehyde, 3, 5‐dibromo‐2‐hydroxybenzaldehyde, 2‐hydroxy‐5‐nitrobenzaldehyde, 5‐chloro‐2‐hydroxybenzaldehyde and 1, 3‐bis(3‐aminopropyl)tetramethyldisiloxane, respectively] were prepared in situ in the presence of a copper(II) salt or by direct complexation between a copper(II) salt and a presynthesised Schiff base. The compounds {CuL 1, CuL 1 · 0.5Py, CuL 2 · 0.375CH2 Cl2, (CuL 3 )[Cu(4‐Me‐Py)4 Cl]Cl· 2H2 O, CuL 4, CuL 4 · CHCl3 and CuL 5, as well as the isolated ligand H2 L 3 } were characterised by elemental analysis, spectroscopic methods (IR, UV/Vis, 1 H NMR, EPR) and X‐ray crystallography. The formation of a 12‐membered central chelate ring in these complexes is effected by the tetramethyldisiloxane unit, which separates the aliphatic chains, thus significantly reducing the mechanical strain in such a chelate ring. We dub this a "shoulder yoke effect" by analogy with the load‐spreading ability of such an ancient device. The coordination geometry of copper(II) in Cu II L 1–5 can be described as tetrahedrally distorted square‐planar. Maximum tetrahedral distortion of the coordination geometry expressed by the parameter τ 4 was observed for CuL 1 (0.460), while distortion was minimal for the two crystallographically independent molecules of CuL 2 (0.219 and 0.284). The Si–O–Si bond angle varies markedly between 169.75(2)° for CuL 1 and 154.2(3)° for CuL 4 · CHCl3 . Charge‐density and DFT calculations on CuL 1 indicate high ionic character of the Si–O bonds in the tetramethyldisiloxane fragment. The new copper(II) complexes bearing the disiloxane moiety have been shown to act as catalyst precursors for the aerobic oxidation of benzyl alcohol to benzaldehyde mediated by the TEMPO radical, reaching yields and TONs up to 99 % and 990, respectively, under mild and environmentally friendly conditions (50 °C; MeCN/H2 O, 1:1). Abstract : New copper(II) Schiff base complexes with a 12‐membered central chelate ring, bearing the disiloxane moiety displaying a "shoulder yoke effect", have been prepared and act as catalyst precursors for the aerobic oxidation of benzyl alcohol to benzaldehyde mediated by the TEMPO radical, reaching yields and TONs up to 99 % and 990, respectively, under mild conditions (50 °C; MeCN/H2 O, 1:1).